PENGEMBANGAN MODEL SIMULASI GELOMBANG MENGGUNAKAN MICROSOFT EXCEL SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA KELAS XI - Lia Wijaya; Partono; Dedy Hidayatullah Alarifin (Universitas Muhammadiyah Metro, 2025)
Abstract: Physics is one of the subjects that is quite abstract and difficult for students to understand, especially in wave material. So it requires relevant learning media to help students understand the material to be delivered. This study aims to overcome the limitations in the delivery of wave material through the development of a wave simulation model design using Microsoft Excel as a learning media, then test the feasibility and level of attractiveness of the model. This research was designed using the Research and Development (R&D) research method based on the 4-D research model. The research respondents were Class XI of SMA Negeri 1 Rumbia in the 2024/2025 academic year. This research and development produces a final product in the form of physics learning media for wave material based on Microsoft Excel. This wave learning media can present simulations of transverse waves, longitudinal waves, and wave superposition made using the developer menu. The learning media that has been made is then validated by experts, namely media experts and material experts. Media expert validation obtained a percentage of 88.94% with very feasible eligibility criteria, while material expert validation obtained a percentage of 85.11% with very feasible eligibility criteria, and the results of small group trials obtained a percentage of 86% with very feasible eligibility criteria.